Abordagens para a Modelagem do Canal Espaço-Temporal com Vistas a Aplicações de Antenas Adaptativas - Cavalcanti, F. R. P.; Romano, J. M. T. (Journal of Communication and Information Systems, 2018)
In this paper we discuss the space-time channel modeling aiming applications of adaptive antennas in mobile communication systems. Some classical approaches for this sake are reviewed and the underlying assumptions discussed. A model that unifies these approaches by including them as particular cases is then presented. Simulation results on adaptive antenna arrays in a TDMA cellular system illustrate the impact of the adoption of each modeling approach in its performance as well as the relationship among them.